The Mediating Role of Digital Transformation in the Effect of Dynamic Capabilities on Business Resilience - Nurhayati, Nurhayati; Astono, Ari Dwi (JDM (Jurnal Dinamika Manajemen), 2024)
The purpose of this research is to investigate the interplay among dynamic capabilities, digital transformation, and business resilience, particularly focusing on micro, small, and medium enterprises (MSMEs) in Indonesia. This study used a survey method to collect the data and then analysed it using Structural Equation Modelling (SEM) to test the hypothesis. The results show that dynamic capabilities and digital transformational positively affect business resilience. Furthermore, digital transformational as a mediator between them. This research provides further suggestions on how dynamic capabilities can improve digital transformational in their business resilience. The conclusion drawn from this study is that dynamic capabilities directly influence digital transformation and contribute to its success. Furthermore, dynamic capabilities indirectly affect business resilience through digital transformation, with digital transformation acting as a mediator in the correlation between dynamic capabilities and business resilience. This finding underscores the significance of dynamic capabilities in driving digital transformation adoption and subsequently enhancing business resilience, particularly in the context of Indonesian MSMEs.